Gamified English learning and students’ spiritual learning behavior: Roles of Wayground use, enjoyment, and interest - Rahmadana; Harmita Sari; Edi Wahyono; Chen Ching Yang (JEELS (Journal of English Education and Linguistics Studies), 2026)
Learning success in gamification era is no longer determined solely by technology, but also by crisis or strength of students’ spiritual learning behavior. This study examines students’ moral-spiritual learning behavior in digital English learning by investigating the effects of Wayground use and Perceived Ease of Use (PEOU), with learning enjoyment and student interest as mediating variables. Although gamified digital platforms have been widely implemented in English language instruction, maintaining students’ consistent and value-oriented learning behavior remains challenging, particularly in vocational education contexts. This study employed a quantitative cross-sectional design using Structural Equation Modeling (SEM). Data were collected through a structured questionnaire administered to one hundred and fifty Indonesian vocational high school students who had experience using Wayground or Quizizz. The findings indicate that Wayground use significantly influences learning enjoyment, student interest, and moral-spiritual learning behavior. In contrast, PEOU does not directly affect moral-spiritual learning behavior, although it significantly predicts learning enjoyment. The results also demonstrate that learning enjoyment and student interest mediate the relationship between Wayground use and moral-spiritual learning behavior. These findings suggest that successful digital English learning is shaped not only by technological usability but also by students’ emotional engagement and internalized values. This study highlights the importance of affective factors in strengthening students’ moral-spiritual learning behavior in gamified English learning environments.